2013
DOI: 10.1016/j.urolonc.2010.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Robot-assisted laparoscopic partial nephrectomy for tumors greater than 4 cm and high nephrometry score: Feasibility, renal functional, and oncological outcomes with minimum 1 year follow-up

Abstract: Objectives Minimally invasive robotic assistance is being increasingly utilized to treat larger complex renal masses. We report on the technical feasibility and renal functional and oncological outcomes with minimum 1 year follow up of robot-assisted laparoscopic partial nephrectomy (RALPN) for tumors greater than 4 cm. Methods and Materials The urologic oncology database was queried to identify patients treated with RALPN for tumors greater than 4 cm and a minimum follow up of 12 months. We identified 19 RA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
71
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(79 citation statements)
references
References 25 publications
(28 reference statements)
6
71
0
1
Order By: Relevance
“…26 Few studies on highly complex RCC are available, and most with short follow-up, therefore whether the correlation between adverse pathological findings/poor survival outcome and higher nephrometry score is stronger than that with higher TNM stage is still debated. In a study on 80 patients treated 27 In another study of 19 RPN in RCC with moderate-high nephrometry score, 28 no increased progression rate was found, but with a median follow-up of 22 months only. In the current study, 5 year RFS and CSS were 90.8% and 96.1% respectively.…”
Section: Discussionmentioning
confidence: 92%
“…26 Few studies on highly complex RCC are available, and most with short follow-up, therefore whether the correlation between adverse pathological findings/poor survival outcome and higher nephrometry score is stronger than that with higher TNM stage is still debated. In a study on 80 patients treated 27 In another study of 19 RPN in RCC with moderate-high nephrometry score, 28 no increased progression rate was found, but with a median follow-up of 22 months only. In the current study, 5 year RFS and CSS were 90.8% and 96.1% respectively.…”
Section: Discussionmentioning
confidence: 92%
“…RPN has been demonstrated to be safe and feasible for challenging renal tumors, such as large and hilar renal masses. 6,7,19 The aim of our study was to demonstrate the feasibility of RPN for tumors > 4 cm and to emphasize that robotic assistance may offer advantages even for surgeons who are experienced in minimally invasive techniques.…”
Section: Petros Et Almentioning
confidence: 99%
“…Patients with tumors > 4 cm had a longer median WIT (25 vs 20 min, P = 0.011). Gupta and coworkers 7 reported on 17 patients with tumors > 4 cm (median tumor size, 5 cm), with a median EBL of 500 mL, median operative time of 390 minutes, and median WIT of 36 minutes. They attributed these outcomes to a higher median nephrometry score of 9 (6-11), a multifocality rate of 42%, and the fact that 89.5% of tumors were > 50% endophytic.…”
Section: Petros Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…49 Gupta et al similarly reported no local or metastatic recurrences following RPN at a median follow-up of 22 months. 78 Despite these early promising data for RPN, some studies have also shown a higher, albeit statistically insignificant, occurrence of positive surgical margins 79 Early studies had demonstrated an insignificant oncologic effect of PSM with respect to local or metastatic recurrence, 80,81 but emerging data conflict with these earlier findings. 82 Pending further studies on the oncologic significance of PSM during PN, meticulous and complete surgical resection with close follow-up of patients with known PSM is recommended.…”
Section: Oncologic Outcomesmentioning
confidence: 99%